Place and Time in Argumentation - Tindale, Christopher W. (Cham : Springer Nature Switzerland : Imprint: Springer, 2022)
This book introduces the principles of place and time by discussing the main roles they play in argumentation, unpacking the multifarious meanings of spatiality and temporality. Definitions of kairos are explored to yield suggestions as to how this concept, and that of 'place', can operate in argumentation. The chapters explore various related concepts such as the role of different arguments in different places, and how some places are not intended for argument; argumentation, time and temporality; visual argumentation; the effect of the passage of time on argument evaluation; and the image as a site of discursive production. This collection is of interest to students and researchers in argumentation studies, rhetoric, reasoning, and philosophy. Previously published as a Special Issue in the journal: Argumentation "Special Issue Title: Of Place and Time" .
Introduction: Of Place and Time -- Place as Argument -- Argumentation and the Challenge of Time: Perelman, Temporality, and the Future of Argument -- An Early Renaissance Altarpiece by Domenico Veneziano: A Case of Visual Argumentation? -- On the Puzzling Death of the Sanctity-of-Life Argument -- Place, Image and Argument: The Physical and Nonphysical Dimensions of a Collective Ethos -- Arguing Terror.
Keywords: Philosophy; Language and languages-Style.; Rhetoric; Logic; Culture-Study and teaching; Philosophy; Rhetorics; Logic; Visual Culture; Cultural Theory